2011
DOI: 10.1186/1471-2180-11-221
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomic study of methanotrophic microorganisms in Coal Oil Point seep sediments

Abstract: BackgroundMethane oxidizing prokaryotes in marine sediments are believed to function as a methane filter reducing the oceanic contribution to the global methane emission. In the anoxic parts of the sediments, oxidation of methane is accomplished by anaerobic methanotrophic archaea (ANME) living in syntrophy with sulphate reducing bacteria. This anaerobic oxidation of methane is assumed to be a coupling of reversed methanogenesis and dissimilatory sulphate reduction. Where oxygen is available aerobic methanotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 65 publications
(95 reference statements)
2
34
0
1
Order By: Relevance
“…Other studies have reported genomic data from anaerobic methane oxidizing archaea in the ANME-1 group (Hallam et al 2004;Meyerdierks et al 2010;Meyerdierks et al 2005), and a recent metagenomic survey similar to ours also found that most ANME sequences were related to those from ANME-1 (Havelsrud et al 2011). Using a PCR-based approach another study also found mostly ANME-1 (Lloyd et al 2011).…”
Section: Resultssupporting
confidence: 83%
“…Other studies have reported genomic data from anaerobic methane oxidizing archaea in the ANME-1 group (Hallam et al 2004;Meyerdierks et al 2010;Meyerdierks et al 2005), and a recent metagenomic survey similar to ours also found that most ANME sequences were related to those from ANME-1 (Havelsrud et al 2011). Using a PCR-based approach another study also found mostly ANME-1 (Lloyd et al 2011).…”
Section: Resultssupporting
confidence: 83%
“…Methylomirabilis oxyfera"-like bacteria in marine sediments based on genomic analyses, but this was only based on 16S rRNA reads and no similarity with functional genes (for methane monooxygenase) of "Ca. Methylomirabilis oxyfera" could be found in the metagenome (24). The contribution of "Ca.…”
Section: Discussionmentioning
confidence: 85%
“…Functions such as sulfate reduction in hydrothermal vents and cold seeps have been mainly attributed to ε-and δ-Proteobacteria (Desulfococcus and Desulfosarcina) (Longnecker and Reysenbach, 2001;Inagaki et al, 2002;Zeng et al, 2005), sulfur oxidation to γ-and ε-Proteobacteria (Inagaki and Nakagawa, 2008), methane oxidation to members of the uncultured candidate division JS1 (Inagaki et al, 2002), γ-and α-Proteobacteria (Xu et al, 2005) and dechlorination to members of δ-Proteobacteria and Chloroflexi (Inagaki and Nakagawa, 2008). Archaea are also crucial players in the chemosynthetic activity of the DSS microbial community, e.g., in the fixation of dissolved inorganic carbon (Herndl et al, 2005), methane oxidation (Havelsrud et al, 2011) and nitrification (Beman et al, 2008). Archaea have also been shown to be relatively more abundant in DSSs microbial communities (Herndl et al, 2005).…”
Section: Features Referencesmentioning
confidence: 99%